2009
DOI: 10.1590/s1806-37132009000900003
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics associated with complete surgical resection of primary malignant mediastinal tumors

Abstract: Objective: To identify preoperative characteristics associated with complete surgical resection of primary malignant mediastinal tumors. Methods: Between 1996 and 2006, 42 patients with primary malignant mediastinal tumors were submitted to surgery with curative intent at a single facility. Patient charts were reviewed in order to collect data related to demographics, clinical manifestation, characteristics of mediastinal tumors and imaging aspects of invasiveness. Results: The surgical resection was considere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…Negative margin was achieved in 75% of our patients with large anterior mediastinal mass, comparable to a mediastinal tumor series by Gross et al which reported 69.1% complete resection rate (18). There are no other large anterior mediastinal mass series for comparison at the time of writing.…”
Section: Discussionsupporting
confidence: 82%
“…Negative margin was achieved in 75% of our patients with large anterior mediastinal mass, comparable to a mediastinal tumor series by Gross et al which reported 69.1% complete resection rate (18). There are no other large anterior mediastinal mass series for comparison at the time of writing.…”
Section: Discussionsupporting
confidence: 82%
“…Overall survival in five years is significantly better among patients submitted to complete surgical resection (84.4% vs. 42.9%). 1 Aortoesophageal fistula (AEF) is a rare but fatal cause of gastrointestinal hemorrhage. 2 Management of a patient with AEF requires rapid diag-nosis and emergent intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, the authors did not go into details, but apparently all cases were small encapsulated thymomas. In the last decade, two case series reporting on management and outcomes of thymic tumors in Latin America were published, one in Brazil (16) and one in Chile (17). The Brazilian study included 26 patients with thymic malignancies operated on from 1986 until 2006.…”
Section: Mis For Thymic Procedures In Latin Americamentioning
confidence: 99%
“…The Brazilian study included 26 patients with thymic malignancies operated on from 1986 until 2006. In no case was the VATS approach used (16). The Chilean study included 54 patients with thymic tumors (thymomas or thymic carcinomas) from 2000 to 2010, of which 47 underwent resection.…”
Section: Mis For Thymic Procedures In Latin Americamentioning
confidence: 99%